Efficacy of medical therapy in the initial management of acute primary angle closure in Asians - Ramli, N.; Chai, S.M.; Tan, G.S.; Husain, R.; Hoh, S-T.; Ho, C-L.; Aung, T. (Nature Publishing Group, 2010)
Purpose Recent studies have advocated the use of laser iridoplasty or paracentesis in the initial management of patients with acute primary angle closure (APAC). The aim of this study was to ascertain the effectiveness of medical treatment consisting of topical and systemic intraocular pressure (IOP)-lowering agents in the initial management of APAC. Methods This was an observational case series of consecutive patients presenting with APAC at a Singapore hospital over 2 years. On diagnosis, all subjects received intravenous acetazolamide followed by oral acetazolamide, topical pilocarpine, timolol, and steroid eye drops. Resolution of APAC was defined as IOP <21 mm Hg with no acute symptoms. Results In all, 134 consecutive APAC subjects were studied. The majority of subjects were Chinese (96.3%) and female (80%), and the mean age was 63.7 +/- 9.6 years. The mean presenting IOP was 58 +/- 12.7 mm Hg and mean duration of symptoms was 2.8 +/- 3.2 days. With medical therapy, APAC attacks resolved within 3, 6, 12, and 24 h in 28 (21.5%), 58 (44.6%), 99 (76.2%), and 116 (89.2%) subjects, respectively. After resolution of APAC, laser iridotomy was performed in 81.6% of the subjects; 16.2% of the subjects underwent cataract extraction. There was failure of resolution of APAC in only 3 subjects (2.2%). No subject suffered any serious side effects as a result of treatment. Conclusions Medical therapy resulted in resolution of APAC within 12 h in 76.2% of the subjects and within 24 h in 89.2% of the subjects, showing the effectiveness of medical therapy in the initial management of APAC. Eye (2010) 24, 1599-1602; doi:10.1038/eye.2010.92; published online 25 June 2010